2022
DOI: 10.3389/fpls.2022.1010404
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and expression profiles of jasmonate ZIM-domain gene family provide insight into abiotic stress resistance in sunflower

Abstract: Jasmonate ZIM-domain (JAZ) proteins act as inhibitory factors of the jasmonic acid (JA) pathway, which is involved in regulating plant development and defense responses. However, there are no extensive studies available on JAZ genes in sunflower (Helianthus annuus L.). In this study, the phylogenetic analysis of 139 putative JAZ genes from eight plants demonstrated that these JAZs could be divided into five groups (Groups I–V), and the 27 sunflower JAZs (HaJAZs) were classified into these five groups. All grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…The variation in exon‒intron numbers and conserved motifs within gene families often provides valuable insights into the evolutionary mechanisms of those gene families ( Abdullah-Zawawi et al, 2021 ; Song et al, 2022 ). In the investigation of SAP genes across seven Compositae species, it was observed that members of the same subfamily exhibited similar exon‒intron numbers and conserved motifs, suggesting shared biological functions within subfamilies.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in exon‒intron numbers and conserved motifs within gene families often provides valuable insights into the evolutionary mechanisms of those gene families ( Abdullah-Zawawi et al, 2021 ; Song et al, 2022 ). In the investigation of SAP genes across seven Compositae species, it was observed that members of the same subfamily exhibited similar exon‒intron numbers and conserved motifs, suggesting shared biological functions within subfamilies.…”
Section: Discussionmentioning
confidence: 99%
“…The exon–intron organizations and conserved motifs were visualized with TBtools (v1.108) [ 37 ]. The online PlantCARE database ( http://bioinformatics.psb.ugent.be/webtools/plantcare/html/ ) was used to determine the putative cis -acting regulatory elements, as described previously [ 38 ].…”
Section: Methodsmentioning
confidence: 99%